Sugar and coffee in São Paulo: Family and household structure in Itu and Areias in 1829 - Herbert Klein; Francisco Vidal Luna (Revista Brasileira de Estudos de População)
Abstract This essay examines the impact of commercial sugar and coffee exports on household and family structures in two São Paulo’s production centers in the second decade of the nineteenth century. Using manuscript household census records this study also explores how these economies shaped the color, sex, age, civil status, and legal standing of these two distinct populations. In 1829, Areias and Itu were at two different stages of their development in sugar and coffee production. How these differences in economic conditions shaped social structures and domestic life in these prominent production centers of the time is the basic theme of this study.